ศึกษาการออกแบบ ทดสอบและปรับปรุง เครื่องดักฝุ่นแบบเปียกชนิดหอแผ่นปะทะ - นิรุต ปัญญาสิทธิ้ (จุฬาลงกรณ์มหาวิทยาลัย, 2000)
This research is the study of design, testing and development of a plate tower wet scrubber which is 12 m. height,64 m2crossection area. The plate tower wet scrubber function as a particles collecting in flue gas from bagasses combustion at 250 X103 kg-steams per hour water tube boiler. In the testing to study the water to flue gas ratio and space area of the buffer plate 1 that effect to pressure drop across a plate tower wet scrubber and overall collecting efficiency. The experiment results can be summarized as follows. 1.The gas pressure drop across a plate tower wet scrubber will increase when the liquid to gas ratio increase. The gas pressure drop range 15-140 mmH2O for space area of the buffer plate is 24 m2 and the gas pressure drop range 5-117 mmH20 for space area of the buffer plate is 36 m2. 2.The overall collecting efficiency will increase when the liquid to gas ratio increase and the maximum efficiency is 90 % at the water to flue gas ratio equal to 7x10-4 m3 water / m3 flue gas or more than 7 x10-4m3 water / m3 flue gas.